2015
DOI: 10.1111/jsm.12793
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in microRNA Expression in a Murine Model of Diet-Induced Vasculogenic Erectile Dysfunction

Abstract: Introduction MicroRNAs (miRs) are noncoding, endogenous RNA molecules that regulate gene expression and play roles in response to vascular injury. Aim The aim of this study was to identify miRs expressed in corporal tissue (CT) and to determine whether miRs demonstrate differential expression in a mouse model of diet-induced erectile dysfunction (ED). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Interestingly, miRs, which are novel and potent mediators of tissue injury, and their correlations with various benign urologic pathologies, specifically ED, remain unexplored. 24 Therefore, owing to various evidence and findings, the current study aimed to explore the role of miR-205 in DMED using multiple modes of testing and experimentation. In the current study, we demonstrated that miR-205 contributed to the pathogenesis of DMED by negatively regulating AR Additionally, it was revealed that AR is a target gene of miR-205, and down-regulation of miR-205 or up-regulation of AR significantly improved the erectile functioning of rats suffering from DMED by promoting proliferation as well as inhibiting apoptosis of CSMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, miRs, which are novel and potent mediators of tissue injury, and their correlations with various benign urologic pathologies, specifically ED, remain unexplored. 24 Therefore, owing to various evidence and findings, the current study aimed to explore the role of miR-205 in DMED using multiple modes of testing and experimentation. In the current study, we demonstrated that miR-205 contributed to the pathogenesis of DMED by negatively regulating AR Additionally, it was revealed that AR is a target gene of miR-205, and down-regulation of miR-205 or up-regulation of AR significantly improved the erectile functioning of rats suffering from DMED by promoting proliferation as well as inhibiting apoptosis of CSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the optical density (OD) value at 570 nm of each well was measured using a microplate reader (NYW-96 M, Beijing Nyaw Co., Ltd., Beijing, China). The cell viability curve was plotted with various time intervals(24, 48, and 72 hours) as the abscissa, and the OD values as the ordinate.…”
mentioning
confidence: 99%
“…In addition, miR‐20 and miR‐106a are essential regulators of proliferation and survival of SSC by controlling target genes Stat3 and Ccnd1 at the posttranscriptional level in mice (He et al ., ). And, diet‐induced erectile dysfunction is predominantly regulated by upregulation of expression of five miRNAs such as miR‐151‐5p , miR‐205 , miR‐720 , miR‐1937a , and miR‐1937c (Barbery et al ., ). Consistent with those results, we determined the expression of miRNAs regulating the expression of the Apod gene in reproductive organs of male rats fed either a normal or a high‐cholesterol diet using a miRNA prediction database and quantitative RT‐PCR analyses.…”
Section: Discussionmentioning
confidence: 97%
“…Erectile dysfunction is closely associated with high fat diet‐induced obesity . Recently, a pilot study examined the involvement of miRNAs in high fat diet associated erectile dysfunction in C57BL/6 mice . Following 22 weeks of high fat feeding (60% of total calories from fat), corporal tissue exhibited increased expression of miR‐720, miR‐1937a, miR‐1937c, miR‐205, miR‐151–5p, and decreased expression of miR‐550, miR‐425, miR‐134, miR‐153, and miR‐26b.…”
Section: High Fat Diet‐induced Changes In Mirna Expression In Variousmentioning
confidence: 99%
“…In the skeletal muscle, studies have reported close association between intramuscular triglyceride accumulation and insulin resistance . Other comorbidities associated with excessive weight gain and obesity include: various types of cancers , neuronal damage , endothelial dysfunction , cardiac hypertrophy , and erectile dysfunction . These manifestations of high calorie intake and fat accumulation involve a large panoply of cellular signaling, which itself is driven by various epigenetic modifications.…”
Section: Introductionmentioning
confidence: 99%